SCAR Strategic Plan 2023-2028: Urgent Messages from the South: Antarctic and Southern Ocean Science and Policy ... - Research, The Scientific Committee On Antarctic (Zenodo, 2023)
The Strategic Plan for the Scientific Committee on Antarctic Research (SCAR) from 2023 to 2028. Strategic planning prioritizes the most important areas of potential interest. In response to the global climate emergency, the SCAR Strategic Plan 2023-2028 is weighted toward climate science that can be addressed in the Antarctic. The climate science in this Plan focuses on increasing temperatures, ice sheet melting and sea level rise, as well as impacts on ecosystem function, biodiversity, and human society. Other science topics remain of significant interest to SCAR and the community it supports. Therefore, while climate science is emphasized over the next few years as a matter of urgency, SCAR will continue to maintain and nurture a broad and deep portfolio of science activities, including curiosity-driven science, to reflect the full breadth of Antarctic science and to facilitate creative solutions to future challenges. To realize SCAR’s vision and advance the seven overarching objectives, SCAR will adopt a ...